Testamentary Bequests for Pious Purposes in the Christian Roman Empire - Pál Sáry (Journal on European History of Law)
The document explores the legal capacity of the church to receive bequests for pious purposes within the Christian Roman Empire. It delves into the foundational case where the church was designated as the heir or was bequeathed a legacy or a fiduciary commission by the testator. The eligibility for such bequests was granted to the community responsible for the testator's place of residence. The legal capacity of local communities or churches was recognized following the Constantinian shift around the year 313, marking a significant departure from the prior lack of legal independence and property separation from their members. The document also addresses the initial organization of Christians into burial clubs, a concept later dismissed due to lack of evidence, and the political objectives of Christian Roman emperors to stabilize and financially support the church's status, notably through granting it the ability to inherit through wills.